Penyuluhan Literasi Keuangan Bagi Pemilik UMKM di Kabupaten Pesisir Selatan - Silvy Astari; Mya Yuwanita Suhanda; Howardi Visza Adha; Nanda, Nanda (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The community service held by lecturer at Faculty of Business and Economic, Baiturrahmah Universit. The aims of this activity is to improve financial literacy for Small Medium Enterprise (SME) owners in Nagari Koto Nan Duo, Batang Kapas District, Pesisir Selatan Regency,at August 10, 2024. West Sumatra Province. Financial literacy is include in OJK program that encourage more society understand the concept of financial literacy. We trying to support the program, by providing material such as the important of financial literacy, saving and online loans. We hope that by giving this material to SME owner they could have good financial literacy, make the right financial decisions and avoid things such as illegal online loans that would help the owner to developed their business. The indicator that this activity is success are the participant understand the concept of financial literacy and could make the right decision regarding to their financial problems. We hope that this activity will be done in other region so that there will be more educated SME owner and more SME established.